ANALISIS PELAKSANAAN PEMBELAJARAN BERDIFERENSIASI DI TK AISYIYAH BUSTANUL ATHFAL 06 MEDAN - Cahyati, Annisa; Marbun, Sariana (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2025)
The differentiation process strategy focuses on how children understand or interpret the information or material taught in class. Once the teacher identifies the children's learning needs, abilities, and interests, they can determine the appropriate methods or strategies to be implemented during the learning process. This study aims to analyze teachers' strategies and the inhibiting factors in applying differentiation in the learning process at Aisyiyah Bustanul Athfal 06 Kindergarten, Medan. The research method used is descriptive qualitative research, employing data analysis techniques such as observation, interviews, and documentation. The results of this study reveal that the teachers at Aisyiyah Bustanul Athfal 06 Kindergarten, Medan, have effectively implemented differentiation process strategies, although there are some challenges in applying these strategies.